Demonetization: A Boon or Bane for Indian Economy (Trinity Journal of Management, IT & Media (TJMITM), 2017)
On 8 November 2016, the Government of India announced the  demonetization of all 500 and 1,000 banknotes of the Mahatma  Gandhi Series. The government claimed that the action would  curtail the shadow economy and crack down on the use of illicit  and counterfeit cash to fund illegal activity and terrorism. The  term Demonetization refers to withdrawal of a particular form of  currency from circulation. It is essential whenever there is a  change of national currency. The old unit of currency must be  removed and substituted with a new currency unit.  Demonetization took place for the first time in the year 1946 and  second time in 1978. The currency is demonetized for the third  th time on 8 Nov. 2016 by our honourable Prime Minister Shri  Narender Modi. This is the bold step taken by the govt. for the  furtherance of the economy and to put a full stop on black money,  laundering and illegal transaction amongst the different nations  of the world. The paper discusses the impact of recent  demonetization on the Indian system and also the reasons.
Keywords: Demonetization; Black Money; Effects; Corruption